Values of some Reproduction Indices in Sows Depending on Artificial Insemination Time - Ioan Petroman; Cornelia Petroman; Diana Marin; Ramona Ciolac; D. Bogosel; Ana Lozici; Victoria Serban (Scientific Papers Animal Science and Biotechnologies, 2023)
In order to improve some reproduction indices, we need to implement a farm management that uses at optimum levels the artificial insemination time depending on oestrus period in sows because in the classical oestrus identification programme there are significant differences between fecundity and prolificacy in oestrus females identified as such and artificially inseminated in the morning. In our management programme, females identified in oestrus twice a day and artificially inseminated at shorter time intervals produced higher fecundity indices (88.90±2.51 compared to 87.40±1.25) with similar prolificacy.